2012
DOI: 10.1007/s00344-011-9257-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phytohormone Profiles during Male and Female Cone Initiation and Early Differentiation in Long-shoot Buds of Lodgepole Pine

Abstract: In lodgepole pine (Pinus contorta Dougl. ex Loud. var. latifolia Engelm), cone initiation and gender differentiation are site-specific in long-shoot buds with female cones in the distal portion and male cones in the proximal portion. By using high performance liquid chromatography-electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) in multiple reaction monitoring (MRM) mode, cytokinins, indole-3-acetic acid (IAA), gibberellins (GAs), abscisic acid (ABA) and their selected metabolites, were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
(34 reference statements)
5
1
0
1
Order By: Relevance
“…This fact suggest to us that under long drought periods ABAGE cleavage could be used by these plants to give active ABA; then, once plants are adapted to it, or the stress is reduced, this ABA could be degraded in part to 7?-OH ABA, but especially to PA and DPA. Changes in endogenous PA and DPA in different tissues have been reported (Suttle et al 2012) and, interestingly, spatial and temporal differences have recently been observed in several hormones including auxines, cytokinins, PA and ABAGE (Kong et al 2012). Our results led us to think that Manel genotype is the most sensitive one compared with the other genotypes.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This fact suggest to us that under long drought periods ABAGE cleavage could be used by these plants to give active ABA; then, once plants are adapted to it, or the stress is reduced, this ABA could be degraded in part to 7?-OH ABA, but especially to PA and DPA. Changes in endogenous PA and DPA in different tissues have been reported (Suttle et al 2012) and, interestingly, spatial and temporal differences have recently been observed in several hormones including auxines, cytokinins, PA and ABAGE (Kong et al 2012). Our results led us to think that Manel genotype is the most sensitive one compared with the other genotypes.…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, the high PA and DPA concentrations led us to think that this would be the main route of ABA degradation used by these genotypes. Likewise, as Kong et al (2012) suggest, higher concentrations of ABA metabolites might reflect a more active ABA metabolism. According to Jia et al (1996) and Zhang et al (1997), the rate of ABA catabolism is proportional to the ABA levels in plant tissues so, as more ABA is produced, more ABA is degraded into metabolites as PA.…”
Section: Discussionmentioning
confidence: 96%
“…The ratio between ABA and cytokinins in xylem sap are postulated to play an important 16 role in stress signalling (Alvarez et al 2008, Schachtman andGoodger 2008). The higher ratios of cytokinins to ABA may thus favour faster vegetative growth and female cone formation (Kong et al 2011(Kong et al , 2012. In the results reported here, higher concentrations of cytokinins and lower concentrations of ABA were found in the genotype of a good cone producer than in the poor cone producer, in keeping with previously published studies on lodgepole pine (Kong et al 2011).…”
Section: Effects Of Injected Pgrs On Ratios Of Endogenous Phytohormonessupporting
confidence: 90%
“…PGR treatments resulted in higher endogenous concentrations of zeatin (Z)type cytokinins and lower concentrations of abscisic acid (ABA) and its metabolite, ABA glucosyl ester (ABA-GE). This corroborates earlier investigations (Kong et al 2011(Kong et al , 2012 in which higher concentrations of (Z)-type cytokinins and lower concentrations of ABA favoured 6 female cone formation. Kong et al (2016) found that paste application altered both the number and location of female cones.…”
Section: Introductionsupporting
confidence: 92%
“…(Niu et al, 2013(Niu et al, , 2016; Pinus thunbergii Parl. (Kong et al, 2012), Pinus bungeana Zucc. ex Endel.…”
Section: Introductionunclassified